MORPHOMETRIC VARIABILITY IN THE DIATOM FRAGILARIOPSIS KERGUELENSIS: IMPLICATIONS FOR SOUTHERN OCEAN PALEOCEANOGRAPHY - Cortese G.; Gersonde R. (My University, 2007)
Diatoms play a central role in the ecosystem of the Southern Ocean, where they represent the main producers and carriers of organic carbon and dissolved silicon towards the deep ocean. Variability in space and time of the size of the most abundant species (Fragilariopsis kerguelensis) may directly impact the way this ecosystem functions, and also affect the nutrient balance of the global ocean, as important water masses (e.g. the Antarctic Intermediate Water) get their nutrient signature in this area. We used a biometric approach and analyzed the size variability of F. kerguelensis valves in sixty-four surface sediment samples from the Southern Ocean, in sediment trap samples from a mooring (Site PF3) at the Antarctic Polar Front (APF), and along a nearby piston core (PS1654-2). The average length and valve area of F. kerguelensis displayed a distinct increase in the proximity of the APF, and lower values to the north and south of it, and also changed markedly over seasonal cycles, as diatom blooms and nutrient availability waxe and wane. The last glacial to interglacial transition also witnesses important changes in the general shape and valve size of F. kerguelensis, with specimens from glacial intervals being ca. 30% larger than their interglacial counterparts (195 versus 150 μm2 valve area). A sharp peak in average area and a very specific valve morphology correspond to the first signs of deglaciation and concurring SST (Sea Surface Temperature) increase and sea-ice retreat. The latter, together with melting icebergs, may have contributed dissolved iron to surface waters. The highest average sizes during glacial intervals are higher than what found anywhere in the Southern Ocean today. The newly proposed proxy (valve area and shape of F. kerguelensis) may thus prove useful for the reconstruction of the past position and nutrient characteristics of the APF and "opal belt", a region characterized by high production and export of biogenic silica, in a particularly sensitive and dynamic area such as the Southern Ocean. © 2007 Elsevier B.V. All rights reserved.
Keywords: BIOGENIC SILICA; DIATOM; EXPORT PRODUCTION; MORPHOMETRY; NUTRIENT; SOUTHERN OCEAN